2021
DOI: 10.1111/infa.12396
|View full text |Cite
|
Sign up to set email alerts
|

Temperament moderates the effects of early deprivation on infant attention

Abstract: Institutional care has been shown to increase the risk of attention problems in children, but some children are more sensitive to their environment, both for better and for worse.With this in mind, the current study examined the moderating role of temperament (falling reactivity) between early adversity and attention skills. Six-to 15-month-old infants residing in institutions (n = 63) and infants reared by their biological families from low socioeconomic environments (n = 59) were recruited. The infants' atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Although there has been an increased focus on the relation between sleep and attention in early development, to our knowledge there are no published studies have yet used objective measures in parallel with parent reported sleep to explore the link between sleep and concurrent attention control in infants. Additionally, a recent emphasis has been separately placed on the development of both infant sleep and attention in the context of extrinsic and intrinsic factors such as family environment [ 1 , 26 , 27 ]. There is a growing body of research that shows links between poorer sleep and poorer family functioning, as well as poorer attention and poorer family functioning in typically developing children and paediatric patient populations (e.g., [ 28 , 29 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been an increased focus on the relation between sleep and attention in early development, to our knowledge there are no published studies have yet used objective measures in parallel with parent reported sleep to explore the link between sleep and concurrent attention control in infants. Additionally, a recent emphasis has been separately placed on the development of both infant sleep and attention in the context of extrinsic and intrinsic factors such as family environment [ 1 , 26 , 27 ]. There is a growing body of research that shows links between poorer sleep and poorer family functioning, as well as poorer attention and poorer family functioning in typically developing children and paediatric patient populations (e.g., [ 28 , 29 ]).…”
Section: Introductionmentioning
confidence: 99%